(untitled) (Research, Society and Development, 2022)
The aim is to draw an epidemiological profile of dental professionals in Rio Grande do Norte state (RN), Brazil, in relation to COVID-19 infection during the pandemic. In order to obtain the results, a virtual census was carried out with dental professionals registered in the Regional Board of Dentistry of RN (CRO-RN). An online questionnaire was used for data collection, sent via the official CRO-RN email, the WhatsApp app, SMS messages and posted on the institution’s social media page. Data were collected between February 2020 and May 2021, corresponding mainly to the numbers of the first wave of the disease in Brazil. A total of 567 dentists responded to the questionnaire, with an average age of 36.67 years (SD=9.56). The sample consisted of 515 dentists and 52 dental assistants, namely Oral Health Technicians and Oral Health Assistants (OHTs and OHAs respectively). The COVID-19 contamination index during this period was 25.74% of the sample, with the highest found in the OHTs (37%). The factors contributing to contamination were working in the west of the state (p=0.011) and having little professional experience (p=0.015), among others. With respect to the impact of income, the private sector was the most affected (p<0.0001), where professionals who were unable to work for 1 to 3 months were the most compromised (p<0.0001). The lack of personal protective equipment (PPE) in the workplace was related to the increase in contamination.